Relevance versus reliability of accounting information with unlimited and limited commitment - Barbara Schöndube-Pirchegger; Jens Robert Schöndube (Business Research, 2017)
We consider a two-period LEN-type agency problem. The principal needs to implement one out of two accounting systems. One emphasizes relevance, the other reliability. Both systems produce identical inter-temporally correlated signals. The relevant system reports an accounting signal in the period in which it is produced. The reliable system reports a more precise signal, but with a one period delay. Accounting information is contractible only if it is reported within the two-period horizon of the game. Accordingly, accounting information produced in the second period becomes uncontractible with the reliable system in place. Non-accounting information needs to be used for contracting to provide any second period incentives at all.Wederive optimal compensation contracts in a full and in a limited commitment setting. With full commitment, the reliable system trades-offmore precise first and less precise second-period contractible information, as compared to the relevant system. If the reduction of noise in the accounting signals is strong and the distortion in the non-accounting measure is weak, the reliable system is preferred. With limited commitment we identify a similar trade-off if intertemporal correlation of the signals is negative. If it is positive, this tradeoff might reverse: The reliable system is possibly preferred if noise reduction is small and the non-accounting measure is heavily distorted. Noisiness in performance measures then serves as a commitment device. It reduces otherwise overly high powered incentives and thus benefits the principal.
Keywords: M4; D8; C7; 650; Accounting information; Agency-problem; Limited commitment; Timeliness